Non‐vitamin K oral anticoagulants versus warfarin for left atrial appendage thrombus resolution in nonvalvular atrial fibrillation or flutter. Issue 9 (6th August 2019) - Hussain, Aliza; Katz, William E.; Genuardi, Michael V.; Bhonsale, Aditya; Jain, Sandeep K.; Kancharla, Krishna; Saba, Samir; Shalaby, Alaa A.; Voigt, Andrew H.; Wang, Norman C.
Abstract: Background: Non‐vitamin K oral anticoagulants (NOACs) have emerged as alternatives to vitamin K antagonists in select situations. For left atrial (LA) appendage thrombus in nonvalvular atrial fibrillation (AF) or flutter, guidelines recommend oral anticoagulation (OAC) for at least 3 weeks prior to reassessment. Data comparing NOACs to warfarin in this scenario are scarce. Methods: A retrospective study identified subjects with nonvalvular AF or flutter who were: a) noted to have LA thrombus detected on transesophageal echocardiography (TEE), b) previously not receiving long‐term OAC; and c) evaluated for resolution of LA thrombus by follow‐up TEE between 3 weeks to less than 1 year of the initial TEE. Results: The study included 45 subjects with mean age 63.2 years, 69% male, 78% white race/ethnicity, 42% paroxysmal, and mean CHA2 DS2 ‐VASc score 3.4 ± 1.7. All LA thrombi were confined to the appendage. OAC received included apixaban (3), dabigatran (13), rivaroxaban (6), and warfarin (23), The median follow‐up time to repeat TEE was 67 (interquartile range, 49‐96) days. LA appendage thrombus resolution rates were 76% for the entire cohort, 77% for NOACs, and 74% for warfarin. In univariable logistic regression analysis, LA appendage thrombus resolution was similar for NOACs when compared to warfarin (odds ratio, 1.20; 95% confidence interval, 0.31‐4.69; P  = .79). Conclusions: In patients nonvalvular AF or flutter who were OAC naïve at the time of diagnosis with LA appendage thrombus, complete resolution was similar between NOACs and warfarin.